Radical/Addition polymerization silicone hydrogels with simultaneous interpenetrating hydrophilic/hydrophobic networks. Issue 5 (3rd September 2014) - Xu, Jinku; Yang, Pengfei; Zhang, Leilei; Huo, Guanghua
ABSTRACT Transparent silicone hydrogels with interpenetrating hydrophilic/hydrophobic networks were simultaneously synthesized on the basis of the radical polymerization of the methacrylic monomer of 3‐methacryloxypropyl tris(trimethylsiloxy) silane (TRIS)/N, N‐dimethylacrylamide (DMA) and the addition polymerization of hydroxyl‐grafted polysiloxane (HPSO)/isophorone diisocyanate. The curing temperature was set at 80°C by a differential scanning calorimetry study. The polymerization process was studied by in situ Fourier transform infrared spectroscopy. The results indicate that the curing time was about 4.5 min, and the addition polymerization had a faster rate than radical polymerization. Then, the radical polymerization rate increased rapidly, and this led to instant curing. The interpenetrating polymer network (IPN) silicone hydrogels were characterized by swelling kinetics and dynamic mechanical thermal analysis. The results show that all of the hydrogels reached swelling equilibrium at about 4 h in water, and the IPN silicone hydrogels with a hydrophobic network of HPSO indicated a slower water transport than that of the copolymerization hydrogel of DMA and TRIS. The hydrophobic network was finely dispersed in the hydrophilic network, and the increasing hydrophobic network of HPSO decreased the glass‐transition temperature of the IPN silicone hydrogels. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41399.